Empowering People in Creating Generative Forest Permaculture for Conservation and Mitigation Climate Change - Krisdianto Krisdianto; Witiyasti Imaningsih; Ika Oksi Susilawati; Ismi Saroh; Shofaa Maulida; Muhammad Risqan Fadhillah (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2021)
People need room not just for yards, gardens, microclimate regulators, but increasing the function of space is a wise solution, including overcoming an adverse effect of climate change, flood and land erosion, as known that fluctuation environmental factors still are problems for reducing the risk of ecological disaster. This action aims to implement the Permaculture regenerative forest Miyawaki model to reduce the risk of landslide and flood and gain production from small-scale farming by combining multi-cropping plants. We also expect the productivity of Permaculture located at Hinas Kiri for considering the workforce involved, recycle process in the farming system, and economic gain. In conclusion, about 20 people of 4 families involved in nursery and farming earn a salary of about 100.000.000 per year with a better safe guarantee from natural disasters. In conclusion, homey yard-based Permaculture in Hinas Kiri, as a solution for a small farm sustainable model, Permaculture.